Facile and eco-friendly fabrication of a colorimetric textile sensor by UV-induced photografting for acidic gas detection - Park, Young Ki; Oh, Hyun Ju; Lee, Hee Dong; Lee, Jung Jin; Kim, Jong H.; Lee, Woosung (Journal of Environmental Chemical Engineering, 2022)
For the immediate detection of strong acids, it is advantageous to employ colorimetric textile sensors based on halochromic dyes, as such systems permit the detection of gas leaks with the naked eye. Here, we introduce a UV-induced photografting method to dye cotton fabrics in an eco-friendly manner and to improve the dyeability and wash fastness of halochromic dyes. In this UV photografting method, the radical-sensitive groups of the dye and the fiber were covalently bonded through radicals formed under UV irradiation to greatly reduce dye leaching. Two types of graftable-rhodamine dyes were synthesized by introducing a radical-sensitive group to a rhodamine derivative with a superior pH sensitivity, and textile sensors were fabricated via UV photografting. Subsequently, the eco-friendliness of the UV-induced photografting method and the gas detection performances, durabilities, and reusabilities of the fabricated textile sensors were investigated. All fabricated sensors exhibited distinctive color changes (ΔE >15) under acidic conditions, in addition to an outstanding durability (washfastness level: 4-5, performance retention rate after washing: 91%) and reusability after ten washing/drying cycles. Furthermore, the low consumption of solvent (∼91%), the salt/alkali-free nature of this method, its low energy consumption (∼85%), and the relatively short process time (∼41%) render this UV-induced photografting technique more environmentally friendly than conventional dyeing methods. Our results therefore indicate that textile sensors fabricated using the UV-induced photografting method are promising candidates for acid gas sensors in a wide range of applications.
Keywords: Acidic gas; Acidic gas detection; Colorimetric textile sensor; Eco-friendly; Gas detection; Photo-grafting; Rhodamine; Textile sensors; UV induced; UV-photografting; Acidic gas detection; Colorimetric textile sensor; Cotton fiber; Eco-friendly; Photografting; Rhodamine